Effect of Frying Temperatures and Times on the Quality and Flavors of Three Varieties of Lentinus edodes - Yan Chen; Yaping Wang; Qinglin Guan; Xiaoli Zhou (Foods)
The effects of frying times (1, 2, 3, and 4 min) and temperatures (140, 160, 180, and 200 °C) were investigated on the nutritional components, color, texture, and volatile compounds of three Lentinula edodes varieties (808, 0912, and LM) from Guizhou, China. Increased frying time and temperature significantly reduced the moisture, polysaccharide, and protein contents, while increasing hardness and chewiness, and decreasing elasticity and extrusion resilience, negatively impacting overall quality. Optimal umami and sweet amino acid retention were achieved by frying at 160 °C frying for 1–3 min or 140–180 °C for 2 min. Nine volatile compounds were identified, with sulfur-containing compound levels decreasing and ketone, aldehyde, pyrazine, and other volatile compound levels increasing as frying progressed. At temperatures above 180 °C, variety 808 displayed a duller appearance, while variety LM experienced significant water and protein loss, making them unsuitable for frying under these conditions. Conversely, variety 0912 demonstrated superior characteristics, such as retaining higher levels of aspartic acid and sulfur-containing compounds, resulting in a sweeter taste. Overall, frying for 2–3 min at 160–180 °C can preserve high nutritional quality and taste and enhance flavor characteristics relatively well. These findings provide a theoretical basis for the deep processing and utilization of Lentinula edodes and for standardized industrial production.